Multiphase dolomitization in the Jutana Formation (Cambrian), Salt Range (Pakistan): Evidences from field observations, microscopic studies and isotopic analysis - S. Khan; M.M. Shah (Geologica Acta, 2019)
Excellent dolomite exposures are observed in the eastern Salt Range (Pakistan), where the Cambrian Jutana Formation consists of two distinct units (i.e. oolitic – pisolitic unit and massive dolomite unit). Field observations revealed that the lower, oolitic-pisolitic unit mostly comprises medium to thick bedded, interlayered brown yellowish dolostone containing ooids/pisoids and faunal assemblages, and grey whitish sandstone with distinct depositional sedimentary features (i.e. trough-, herringbone- and hhummocky crossbedding). The upper massive dolostone unit consists of thick bedded to massive dolostone. These two units are separated by shale. Petrographic studies identified three dolomite types, which include: fine crystalline dolomite (Dol. I), medium-coarse crystalline dolomite (Dol. II) and fracture associated, coarse crystalline dolomite (Dol. III). Stable isotope studies indicate less depleted δ18O values for Dol. I (-6.44 to -3.76‰V-PDB), slightly depleted δ18O values for Dol. II (-7.73 to -5.24‰V-PDB) and more depleted δ18O values for Dol. III (-7.29 to -7.20‰V-PDB). The δ13C values of the three dolomite phases are well within the range of Cambrian sea-water signatures. Furthermore, δ26Mg-δ25Mg signatures (Dol. I; δ26Mg=-1.19 to -1.67, δ25Mg=-0.61 to -0.86 and Dol. II; δ26Mg=-1.34 to -1.59, δ25Mg=-0.70 to -0.83) indicate three phases of dolomitization in different diagenetic settings. First, an initial stage of dolomitization during the early Cambrian resulted from altered marine, Mg-rich fluids associated with the mixing zone mechanism. Second, a late stage of dolomitization was associated with burial during late Permian. A third dolomitization phase was related to post-Eocene times.